Use and Acceptance of Social Technologies by Internet Banking Services Users in the Middle East - Del-Águila-Obra, Ana Rosa; Padilla-Meléndez, Antonio; Abouseada, Ahmad (My University, 2014)
Bankers worldwide are interested in user´s behaviour in adopting technology-enhanced banking services. This paper analyses the factors that affect the adoption of social technology by users of internet banking services in the Middle East context. The Technology Readiness and Acceptance Model is applied to data from a survey of 338 users in Egypt, Jordan, Kuwait, Lebanon and Saudi Arabia. Findings indicate that technology readiness plays an important role in forming the perceived ease of use. Another main finding is that, contratry to previous research, only perceived ease of use and playfulness influence on the intention to continuous use of these services.
Keywords: Bancos; Internet; Social Media; Internet banking